Modulatory effects of black jujube melanoidins on gut microbiota and metabolic pathways in high-fat diet-induced obesity - Che, Xi; Zhao, Yifei; Wang, Yuxiao; Sun, Xin; Tao, Hongxun; Zhang, Rentang (Frontiers in Nutrition, 2025)
IntroductionObesity, a growing public health issue, is closely associated with excessive energy intake and gut microbiota imbalances. Despite the increasing attention given to black jujube as a blackened fermented food in recent years, the role of its melanoidins (MLD) in obesity-related biological mechanisms has yet to be thoroughly investigated.MethodsThis study investigated the effects of black jujube MLD on obesity induced by a high-fat diet in C57BL/6J mice. We hypothesize that MLD exerts an anti-obesity effect, potentially mediated by alterations in gut microbiota composition and the modulation of metabolic responses.ResultsThe results demonstrate that MLD administration mitigated HFD-induced weight gain, improved insulin resistance, and enhanced glucose metabolism by reducing blood glucose and insulin levels (p < 0.05). MLD also protected the liver, as evidenced by a 16.4% decrease in alanine aminotransferase (ALT) levels and a 29.6% decrease in aspartate aminotransferase (AST) levels (p < 0.05). Furthermore, MLD treatment restored the compromised intestinal microbiota to a healthier state at the genus level by lowering the Firmicutes/Bacteroidetes ratio (38.9%), suppressing the abundance of pathogenic bacteria, such as Erysipelatoclostridium and Bacteroides descendants, and promoting the growth of beneficial bacteria, including Bifidobacterium and norank_f_Muribaculaceae. Metabolomic profiling revealed that MLD can alleviate metabolic disorders by downregulating arginine metabolism and sphingolipid metabolism. Its metabolites are significantly correlated with several bacterial genera, including Bacteroides, Roseburia, Erysipelatoclostridium, Bacteroides, norank_f_Muribaculaceae, and Lachnospiraceae NK4A136 group.DiscussionBased on these findings, MLD may mitigate obesity and other associated metabolic disorders by modulating the gut microbiome–metabolism axis.